Associations between methamphetamine use and lack of viral suppression among a cohort of HIV-positive persons who inject drugs in Hai Phong, Vietnam. (1st November 2020) - Feelemyer, Jonathan; Arasteh, Kamyar; Huong, Duong T.; Oanh, Khuat T.H.; Khue, Pham M.; Giang, Hoang T.; Thanh, Nham T.T.; Moles, Jean Pierre; Vinh, Vu H.; Vallo, Roselyne; Quillet, Catherine; Rapoud, Delphine; et al.
Abstract : Objective: We assessed the association between methamphetamine use and lack of viral suppression among a cohort of HIV-seropositive persons who inject drugs (PWID) in Hai Phong, Vietnam. Design: Cohort study with random effects logit modeling and mediation analysis for antiretroviral therapy (ART) adherence. Methods: PWID were recruited from October 2016 to October 2017; HIV-seropositive PWID were enrolled in a cohort to assess HIV viral loads, changes in drug use, risk behaviors, and ART adherence during 24-month follow-up. Methamphetamine use in last 30 days was divided into three categories: 0 days (no use), 1–19 days (intermediate), and 20 or more days (heavy). Bivariate and a multivariable random effects logit models were used to assess the relationship between methamphetamine use and not being virally suppressed. We also assessed self-reported ART adherence as a mediating factor. Results: A total of 645 HIV-seropositive PWID were included at baseline; 95% male, average age 40 (SD = 6.4). At baseline, methamphetamine use in last 30 days was 64% no use, 32% intermediate use, 4% heavy use. Approximately 74% of PWID reported high/complete adherence; 76% were at viral suppression. In random effects analysis, recent methamphetamine use was associated with not being virally suppressed during follow-up (adjusted odds ratio: 1.84, 95% confidence interval: 1.06, 3.17); the effect was not explained by a mediating effect of self-reported adherence to ART. Conclusion: Recent methamphetamine use is associated with not being virally suppressed among PWID. The results of this study indicate the need for targeted interventions for methamphetamine use with special focus on those with HIV infection.